INFORMATION PROVISION OF INVESTMENT ATTRACTIVENESS REAL ESTATE AT THE REGIONAL LEVEL - Holovachov, V.; Hrytskov, Е.; Mingming, Wen (Municipal economy of cities. Series: «Economy science», 2022)
It has been proven that the level of investment attractiveness of real estate affects the formation and use of real estate. It is an important factor in attracting investment resources to the system of regional development. Of particular importance is the creation of a quantitative basis using mathematical tools. The purpose of the study is to form informational support for the investment attractiveness of real estate at the regional level. To achieve the goal, the following tasks are solved: creation of a quantitative basis for forming the investment attractiveness of real estate at the regional level. application of mathematical tools for the creation of information support for the formation of the investment attractiveness of real estate at the regional level. It was established that the value of the integral indicator I(3) does not depend on the choice of the basic indicator, but depends only on the range of values of groups of indicators by region. Larger values of the integral indicator are observed in regions in which the geometric mean calculated group values of indicators of information provision of investment attractiveness of real estate at the regional level are the largest (that is, have the largest deviation from the minimum). The choice of the method of calculating the integral indicator depends on the purpose of further analysis. In the opinion of the authors, the integral indicator I(3) best meets the given task for the assessment of information provision of investment attractiveness of real estate at the regional level. Unlike the integral indicators I(1) and I(2), there is no need to choose any region as the base for any feature. The absolute deviation characterizes the level of change, and not its direction (more or less than the baseline), therefore it cannot be used to build a simulation model with the aim of reaching predetermined values of the indicators.